Replication of Deoxyribonucleic Acid in Escherichia coli C Mutants Temperature Sensitive in the Initiation of Chromosome Replication - Sakai, Hiroshi (1974)
An Escherichia coli HF4704S mutant temperature sensitive in deoxyribonucleic acid (DNA) synthesis and different from any previously characterized mutant was isolated. The mutated gene in this strain was designated dnaH. The mutant could grow normally at 27 C but not at 43 C, and DNA synthesis continued for an hour at a decreasing rate and then ceased. After temperature shift-up, the increased amount of DNA was 40 to 50%. When the culture was incubated at 43 C for 70 min and then transferred to 27 C, DNA synthesis resumed after about 50 min, initiating synchronously at a fixed region on the bacterial chromosome. The initiation step in DNA replication sensitive to 30 μg of chloramphenicol per ml occurs synchronously before the resumption of DNA replication after the temperature shift-down, being completed about 30 min before the start of DNA replication. When the cells incubated at 27 C in the presence of 30 μg of chloramphenicol per ml after the temperature shift-down to 27 C were transferred to 43 C with simultaneous removal of the antibiotic, no resumption of DNA replication was observed. When the culture was returned to 43 C after being released from high-temperature inhibition at 30 min before the start of DNA replication, no recovery replication was observed; whereas at 20 min, the recovery of replication was observed. These results indicated that HF4704S was temperature sensitive in the initiation of DNA replication. Analysis of HF4704S, by an interrupted conjugation experiment, indicated that gene dnaH was located at about 64 min on the E. coli C linkage map. In E. coli S1814 (a K-12 derivative), which was a dnaH(ts) transductant from HF4704S (C strain) with phage P1, the mutated gene (dnaH) was demonstrated to be closely linked to the thyA marker by conjugation and P1 transduction experiments and to be distinct from genes dnaA through dnaG.